Current Progresses on SVC and STATCOM Applications in the Electrified Railway - 万庆祝; 张辉; 陈建业; 吴命利; 朱桂萍; 王科 (Kongzhi Yu Xinxi Jishu)
With the rapid development of high-speed railway in China, power quality problems, including negative sequence, power unbalance of traction feeders, etc. ,caused by the traction power-supply load are more serious, which becomes one of the constraints to safe and stable operation for the power system and high-speed rail. Practical applications of SVC and STATCOM in electrical railways are set forth and compared. The way fit in current applications for high-speed rail is proposed.